HUMAN HEALTH RISK ASSOCIATED WITH THE TRANSFER OF HEAVY METALS INTO THE TROPHIC CHAIN BY CATTLE GRAZING ON THE AREA IN THE VICINITY OF THE TAILING PONDS IN THE EAST OF BAIA MARE CITY, ROMANIA - SMICAL, Irina; MUNTEAN, Adriana; TÖRÖK, Zoltán (Studia Universitatis Babeș-Bolyai Chemia, 2016)
In order to assess the potential human health risk associated with the transfer of heavy metals from contaminated soil to the trophic chain, several studies were conducted regarding the contaminants known to be associated to the non-ferrous ores processing industry in Eastern Baia Mare: Cu, Mn, Zn, Pb, Cd, Cr and Ni. The transfer of heavy metals into the trophic chain has the following order: from soil to vegetation: Zn>Cd>Cu>Mn>Pb>Cr>Ni and from vegetation to milk: Zn>Cu>Cd>Pb>Ni>Cr>Mn, respectively. Based on the human risk index (HRI) calculated for each element, it was demonstrated that the ingestion of milk from the cows grassed on the contaminated area does not pose a significant risk for human health.